2010
DOI: 10.1002/we.426
|View full text |Cite
|
Sign up to set email alerts
|

Passive structural control of offshore wind turbines

Abstract: The application of control techniques to offshore wind turbines has the potential to signifi cantly improve the structural response of these systems. A new simulation tool is developed that can be utilized to model passive, semi-active and active structural control systems in wind turbines. Two independent, single degree of freedom (DOF) tuned massdamper (TMD) devices are incorporated into a modifi ed version of the aero-elastic code FAST (Fatigue, Aerodynamics, Structures and Turbulence). The TMDs are located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
146
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(148 citation statements)
references
References 53 publications
0
146
0
2
Order By: Relevance
“…The TMD control method applied to OWT and embedded in FAST was presented in [13]. For a multi DOFs system, the equation of motion can be expressed in terms of Kane's theory.…”
Section: Numerical Model Of Tmdmentioning
confidence: 99%
See 1 more Smart Citation
“…The TMD control method applied to OWT and embedded in FAST was presented in [13]. For a multi DOFs system, the equation of motion can be expressed in terms of Kane's theory.…”
Section: Numerical Model Of Tmdmentioning
confidence: 99%
“…Recently some scholars applied the TMD and MTMD in the research of vibration control of OWTs, e.g. Dinh [11], Stewart [12] and Lackner [13] investigated the behaviour of OWTs under operational loads in consideration of TMD, and summarized the influence of TMD mass, amount and locations. Colwell [14] and Chen [15] validate the effects of TLCD on the OWT response by using numerical and experimental methods, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Jonkman et al [3] investigated the use of the aero-hydro-servo-elastic code FAST developed by National Renewable Energy Laboratory (NREL) to simulate the structural responses for barge-type offshore floating wind turbines in different working conditions. Through integrating a passive control code into FAST, Lackner et al [4] proposed an approach using a TMD configuration in the nacelle of the barge-type offshore floating turbines to achieve the structural vibration mitigation, and the control effectiveness of TMD for Spar and TLP-type were also studied. He et al [5,6] proposed the use of TMDs in nacelle to reduce the structure vibration for the barge-type floating turbines, and the results showed that the tower fore-aft displacements suppression rate was 38.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Passive control techniques have been investigated for structural control of both onshore and offshore wind turbines [11][12][13]. One of the issues associated with the use of passive devices for wind turbine structural control is that they may become ineffective as a result of environmental/operational changes or in the presence of parametric variations.…”
Section: Introductionmentioning
confidence: 99%